SEASONALITY IN THE ASEAN EQUITY MARKETS: IS THERE CONTAGION EFFECT? - Abd-Rahim, Ruzita; Harito, Agus; Nor, Abu Hassan Shaari Mohd. (Jurnal Ekonomi & Studi Pembangunan, 2006)
The objective of this study is to investigate the presence of contagion effect of seasonality in stock markets in the ASEAN region. The study employs the month-end closing prices of each countryâ€™s broad based stock market indexes over the period of January 1988 to December 2005. The analysis begins with the re-examination of the existence of seasonality effect in each equity market, separately. Using Granger causality approach, the study finds evidence of causal linkages in the markets with Singapore as the leader in majority of the cases. The time-series regression analysis suggests the presence of contagion effect in that the stock returns Â¡n Singapore set the trend in three other markets (Malaysia, Thailand, and Indonesia). The study further investigates for causal linkages due specifically to seasonality effect. The results deviate from those of the general market performance with respect to the leader-follower linkages but lend strong support to the view that seasonality effect in some stock markets are contagious. Specifically, seasonality effect in Malaysian stock market tends to be pre-determined by its occurrences in Singapore wad Thailand which in turn tend to be pre-determined by seasonality effect in Indonesia and the Philippines, respectively. From investment standpoint, the findings imply that investors in the follower markets could rely on the trend in the leader markets in the same region in order to improve their chance to exploit the seasonality effect.